Stereotip Melayu Malas dan Pengaruhnya pada Etos Kerja - Novalita Sandy; Puspitawati Puspitawati (Mahesa Research Center, 2019)
This study aims to determine the stereotype Melayu Malas on Ethnic Malay associated with the term